Sex Differences in the In-Hospital Mortality of Patients with Acute Myocardial Infarction: A Cross-Sectional Study in 36 Hospitals Across Germany - Karel Kostev; Nimran Kaur; Sabine Kluge; Marcel Konrad; Jamschid Sedighi; Mark Lüdde (Medicina)
Background and Objectives: Acute myocardial infarction (AMI) is one of the leading causes of mortality worldwide and caused ~1.8 million deaths in the European Union from 2012 to 2020. This study aimed to analyze and quantify sex-based disparities, identifying both clinical and systemic contributors to in-hospital mortality differences between male and female patients. Materials and Methods: This multicenter cross-sectional study from 36 hospitals across Germany included all hospitalized patients aged ≥18 years with admissions between January 2019 and December 2023 and a primary diagnosis of AMI. The primary outcome of the study was the prevalence of in-hospital mortality as a function of sex. Multivariable logistic regression analyses were conducted to assess the associations between female sex as compared with male sex and in-hospital mortality. Results: The present study included 9142 male and 4128 female patients with AMI. Women were significantly older than men (74.4 years versus 67.7 years). The proportion of non-ST elevation (NSTE-MI)-MI was higher in women than in men (70.7% versus 66.7%). Overall, in-hospital mortality was higher in women than in men (8.5% versus 7.1%). In a multivariable regression model, female sex was not significantly associated with in-hospital mortality (OR: 0.89; 95% CI: 0.77–1.04) irrespective of the MI type. Conclusions: There were no significant sex-based differences observed in the in-hospital mortality among patients suffering from AMI in Germany.